A guide of solving mathematic word problem / Nurul Fatin Husna Masseban - Masseban, Nurul Fatin Husna (2013)
Mathematic was one of the ways of life. Learning math not only restricted inside school but in everyday of life. Mathematic was one of the fundamental as one of the subject from primary to secondary school even at university level. This subject proved to be important as it been practice in most aspect in daily life. The practical of mathematic also need in the nation vision in order to achieve a good quality of educated and competent society in the application of mathematic knowledge. In this paper, it focuses on student problem when facing mathematic wording problem. It also involved the guidance as the method to enhance student problem when solving the mathematic word problem. The improvement was by using the interactive courseware as the guidance tool assist with the other multimedia elements inside the courseware.